High-Reliability Thermoreceptors with Minimal Temporal and Spatial Variations Through Photo-Induced Patterning Thermoelectrics - Du, Chunyu; Hu, Yue; Xiao, Xiao; Manshaii, Farid; Liang, Lirong; Chen, Jun; Chen, Guangming (Nano-Micro Letters, 2025)
The development of bionic sensing devices with advanced physiological functionalities has attracted significant attention in flexible electronics. In this study, we innovatively develop an air-stable photo-induced n-type dopant and a sophisticated photo-induced patterning technology to construct high-resolution joint-free p–n integrated thermoelectric devices. The exceptional stability of the photo-induced n-type dopant, combined with our meticulously engineered joint-free device architecture, results in extremely low temporal and spatial variations. These minimized variations, coupled with superior linearity, position our devices as viable candidates for artificial thermoreceptors capable of sensing external thermal noxious stimuli. By integrating them into a robotic arm with a pain perception system, we demonstrate accurate pain responses to external thermal stimuli. The system accurately discerns pain levels and initiates appropriate protective actions across varying intensities. Our findings present a novel strategy for constructing high-resolution thermoelectric sensing devices toward precise biomimetic thermoreceptors. Highlights; 1 A novel photobase generator is specifically designed for the fabrication of high-resolution sensing devices. 2 Similarities in pain perception mechanism between thermoelectric-based artificial thermoreceptor and biological nociceptor. 3 Emulation common nociceptive behaviors and pain response under excessive temperature stimuli.